Influence of Linpro and dietary copper on feedlot cattle performance, carcass characteristics, and fatty acid composition of beef - C.A. Alvarado; C.C. Aperce; K.A. Miller; C.L. Van Bibber; S. Uwituze; James J. Higgins; James S. Drouillard (Kansas Agricultural Experiment Station Research Reports, 2012)
Human diets often contain high levels of saturated fatty acids that can have deleterious health consequences such as obesity, diabetes, and heart disease. In contrast, omega-3 fatty acids, which are essential for human nutrition, are consumed at relatively low levels despite of their positive effects on health. Natural sources of omega-3 fatty acids include fresh legumes, cool-season grasses, flaxseed, and fish oil. In spite of the fact that fresh forages often are a key part of the cattle diet, beef is a relatively poor source of omega-3 fatty acids because of biohydrogenation, the action of microorganisms in the rumen that convert polyunsaturated fatty acids, including the omega-3 fats, into saturated fats. Previous research at Kansas State University has shown that feeding cattle flax-based feeds can increase concentrations of omega-3 fatty acids in beef. Researchers at Colorado State University have reported that elevated levels of dietary copper can inhibit the biohydrogenation process to yield beef with greater proportions of polyunsaturated fatty acids. Our objective was to evaluate whether feeding elevated copper concentrations in conjunction with Linpro (O&T Farms; Regina, Saskatchewan, Canada), a co-extruded blend of field peas and flaxseed, could be used to further improve the levels of omega-3 fatty acids in beef.
Keywords: Cattlemen& #x27; s Day; 2012; Kansas Agricultural Experiment Station contribution; no. 12-231-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 1065; Beef Cattle Research; 2012 is known as Cattlemen& #x27; s Day; Beef; Linpro; Copper; Feedlot cattle performance; Carcass characteristics; Fatty acid